La Sanidad naval española: De Lepanto a Trafalgar - Gracia Rivas, Manuel (Cuadernos de Historia Moderna, 2006)
This article analyses the characteristics of the Spanish Navy’s Health Care System by dividing them in two well differentiated time periods: on the one hand, the 16th and 17th centuries; and on the other, the beginning of the 18th century, following the establishment of the Bourbon dynasty. The medical attendance of the crews, the therapeutic resources, and the functioning of general and ship hospitals, on the occasion of certain military journeys, are some examples of the many aspects studied for each period. It is worth highlighting the foundation of the Royal College of Naval Surgeons of Cádiz (Real Colegio de Cirugía de la Armada en Cádiz) and its consequences, although the reforms undertaken were of a rather ephemeral nature. Finally, the emphasis is put on the need to consider every health care model according to the specific circumstances of each time period.